Emil artin and Helmut Hasse : the correspondence 1923-1958 - Frei, Günther; Lemmermeyer, Franz; Roquette, Peter J.; Frei, Gunther (Contributions in Mathematical and Computational Sciences, 2014)
This volume presents English translations of the letters exchanged between Emil Artin and Helmut Hasse written from 1921 to 1958. The letters are accompanied by extensive comments explaining the mathematical background and providing other essential context. Most letters deal with class field theory and shed new light on the birth of one of its most profound results: Artin's reciprocity law.